Factors that affect the teaching-learning process of the english language in children of the third grade of egb of the 14 de julio - juan abel echeverría educational unit in the academic period 2022-2023. - Valencia De La Cruz, Dayana Maribel (2023)
The present research aims to "determine the institutional factors that affect the teaching and learning process of the English language in third grade students of the 14 de Julio - Juan Abel Echeverría Educational Unit in Ecuador during the academic period 2022-2023." A qualitative approach was employed, using a descriptive method. As for the techniques employed, these included direct observation, interviews and a survey applied to 30 third grade EGB students and two English teachers. The data collection instruments consisted of questionnaires, observation sheets and interview guides to gather the informants' perspectives on the English language teaching and learning process. The results highlighted the importance of teacher training, teaching methodology, lesson planning, use of English as the language of instruction, and resource management. These factors significantly influenced the teaching-learning process, potentially impeding the development of linguistic and communicative competencies. Classroom space, size and layout proved to be key institutional factors affecting the learning of third-year students. Timely interventions are crucial to prevent adverse outcomes and maintain students' interest in language learning.